Arthrinins E–G, Three Botryane Sesquiterpenoids from the Plant Endophytic Fungus Arthrinium sp. HS66 - Su, Xiao-Zheng (Nat Prod Bioprospect, 2020)
Arthrinins E–G (1–3), three new sesquiterpenoids possessing non-isoprenoid botryane skeleton, were isolated from the fermentation of an endophytic fungus named Arthrinium sp. HS66 which colonized in the stems of Isodon xerophilus. Their structures were determined by extensive spectroscopic methods. Furthermore, the structure of 1 was unambiguously confirmed by X-ray diffraction, while those of 2 and 3 were verified through quantum chemical calculation of NMR data and ECD spectra. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13659-020-00248-y) contains supplementary material, which is available to authorized users.